2012
DOI: 10.1007/s00192-012-1720-4
|View full text |Cite
|
Sign up to set email alerts
|

What do we do when a midurethral tape fails? Rediscovery of open colposuspension as a salvage continence operation

Abstract: Open colposuspension is an effective option for treating persistent or recurrent stress urinary incontinence after failed midurethral tape, with a high success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Seven studies on Burch colposuspension for recurrent SUI have reported in a total of 276 cases, with a 76% overall success rate (95% CI AE5.04) (15)(16)(17)(18)(19)(20)(21). According to Amaye-Obu et al, who studied 26 patients, the Burch procedure had a cure rate of 81% (95% CI AE15.08) when it was carried out after one previous failed procedure (any procedure), 25% when it was done after two previous surgeries, and 0% after three previous procedures at a 2-year follow up.…”
Section: Burch Colposuspensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies on Burch colposuspension for recurrent SUI have reported in a total of 276 cases, with a 76% overall success rate (95% CI AE5.04) (15)(16)(17)(18)(19)(20)(21). According to Amaye-Obu et al, who studied 26 patients, the Burch procedure had a cure rate of 81% (95% CI AE15.08) when it was carried out after one previous failed procedure (any procedure), 25% when it was done after two previous surgeries, and 0% after three previous procedures at a 2-year follow up.…”
Section: Burch Colposuspensionmentioning
confidence: 99%
“…In two small retrospective studies of 13 and 16 patients who underwent open and laparoscopic Burch colposuspension after failed suburethral tape procedures, the objective cure rates were 77 and 54%, at a median follow up of 1 year or 24.5 months, respectively (19,20). Nitahara et al studied 60 patients with repeat Burch colposuspension procedure.…”
Section: Burch Colposuspensionmentioning
confidence: 99%
“…Recent evidence suggests that subjective cure rates of 85% can be achieved when open colposuspension is used after an unsuccessful primary tape procedure although the development of de novo detrusor overactivity, known to be increased in patients undergoing repeat surgery, can be as high as 30%. 6…”
Section: Dear Sirmentioning
confidence: 99%
“…The options that are available include a repeat mid urethral sling (either retropubic or transobturator), urethral bulking agents, autologous fascial slings and re‐do colposuspension . A re‐do colposuspension is a sensible choice that is likely to achieve a better success rate than a second tape procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The options that are available include a repeat mid urethral sling (either retropubic or transobturator), urethral bulking agents, autologous fascial slings and re-do colposuspension. 5,6 A re-do colposuspension is a sensible choice that is likely to achieve a better success rate than a second tape procedure. Although, colposuspension is an operation that most gynaecologists have now become deskilled in and rarely perform, mainly due to the popularity of tapes.…”
Section: Introductionmentioning
confidence: 99%